2018
DOI: 10.3765/amp.v5i0.4246
|View full text |Cite
|
Sign up to set email alerts
|

Weighted scalar constraints capture the typology of loanword adaptation

Abstract: This paper discusses three basic ways in which loanwords pattern differently than native vocabulary, with a particular focus on the implicational relationships that hold among generalizations that apply at different degrees of nativization. We argue that the overall typology and the effects of the core-periphery structure are best modeled if constraints are weighted as in Harmonic Grammar (Legendre, Miyata & Smolensky 1990), and violation scores are scaled according to degree of nativization. The implicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 17 publications
(33 reference statements)
0
13
0
Order By: Relevance
“…While Poser analyses these apparent cases of ‘word-internal phrase boundary’ as the result of prosodic prespecification, the proposal in this paper suggests that an alternative analysis without prespecification is possible. More broadly, it predicts similar interactions between lexical exceptionality and other patterns of context-sensitivity that can be modelled through constraint scaling, such as lexical category (Smith 2011) or degree of nativisation (Hsu & Jesney 2017, 2018).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…While Poser analyses these apparent cases of ‘word-internal phrase boundary’ as the result of prosodic prespecification, the proposal in this paper suggests that an alternative analysis without prespecification is possible. More broadly, it predicts similar interactions between lexical exceptionality and other patterns of context-sensitivity that can be modelled through constraint scaling, such as lexical category (Smith 2011) or degree of nativisation (Hsu & Jesney 2017, 2018).…”
Section: Resultsmentioning
confidence: 96%
“…Previous work has shown that many influences on phonological patterns can be successfully modelled by scalar constraints, whose penalties are adjusted on the basis of some contextual property. Constraint scaling can account for a range of phonological patterns that depend on a scale or hierarchy, including continuous phonetic values (Flemming 2001, Cho 2011, McAllister Byun 2011, Ryan 2011), perceptual distance (McCollum 2018), the sonority scale (Pater 2012, 2016, Jesney 2015), trigger and target strength in vowel harmony (Kimper 2011), morphological locality in vowel harmony (McPherson & Hayes 2016), prosodic boundary strength (Hsu & Jesney 2016), distance from prosodic boundaries (Inkelas & Wilbanks 2018), lexical category and frequency (Coetzee & Kawahara 2013, Linzen et al 2013) and degree of nativisation (Hsu & Jesney 2017, 2018).…”
Section: Scalar Constraint Analysis Of Restrictions On ṽXmentioning
confidence: 99%
“…This pattern, however, differs from the core–periphery structures reported so far for natural language. Hsu and Jesney (2018) report that there are three patterns found in the core–periphery model of the lexicon displayed in (10a).
Figure 1:Contemporary Yoruba Phonological Lexicon
…”
Section: Emergence Of New Grammars In Contemporary Yoruba Phonologymentioning
confidence: 99%
“…A major characteristic of the core–periphery model of the lexicon is that phonological generalizations that hold in the core ‘vary in how far they extend into the less nativized periphery’ (Hsu and Jesney 2018, after Holden 1976). It is generally assumed for the core–periphery model in (10a) that native words occupy the core where markedness restrictions native to a language are strictly enforced.…”
Section: Emergence Of New Grammars In Contemporary Yoruba Phonologymentioning
confidence: 99%
“…Stratum-specific faithfulness constraints are used to model stratum-specific behavior, with higher-ranked faithfulness constraints corresponding to more-peripheral strata-in which, therefore, the lower-ranked markedness constraints come to be dominated. The precise details of the nature of faithfulness and markedness constraint interaction for modeling lexical strata are still under debate; see, for example, Inkelas & Zoll (2007) and Hsu & Jesney (2017, 2018 for alternative approaches.…”
mentioning
confidence: 99%